2013
DOI: 10.1159/000354026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Syndrome and Benign Prostatic Hyperplasia in Chinese Patients of Different Age Decades

Abstract: Objectives: To evaluate the relationship between metabolic syndrome (MetS) and annual prostate growth rates in Chinese patients of different age decades with benign prostatic hyperplasia (BPH). Methods: We retrospectively analyzed the clinical data obtained from 1,052 Chinese men with BPH. Overnight fasting venous blood specimens were collected and serum levels of prostate-specific antigen, fasting blood glucose, high-density lipoprotein cholesterol, total cholesterol and triglyceride were recorded. We divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…Evidences showed that inflammatory infiltrates are commonly found in BPH lesions [18,19,20], and these inflammatory cells release cytokines and growth factors that can stimulate the proliferation of stroma and epithelial cells, thus contributing to the development and progression of BPH. Recently, it has been shown that patients affected by MetS are at higher risk of BPH/LUTS [3,4,5], suggesting that MetS has very heterogeneous clinical ramifications. Although the exact nature and origins of the associations between MetS and BPH/LUTS are still poorly understood, chronic inflammation has been proposed as a candidate mechanism at the crossroad between these 2 clinical entities [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidences showed that inflammatory infiltrates are commonly found in BPH lesions [18,19,20], and these inflammatory cells release cytokines and growth factors that can stimulate the proliferation of stroma and epithelial cells, thus contributing to the development and progression of BPH. Recently, it has been shown that patients affected by MetS are at higher risk of BPH/LUTS [3,4,5], suggesting that MetS has very heterogeneous clinical ramifications. Although the exact nature and origins of the associations between MetS and BPH/LUTS are still poorly understood, chronic inflammation has been proposed as a candidate mechanism at the crossroad between these 2 clinical entities [6].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a clinical condition characterized by the coexistence of multiple cardiovascular risk factors including obesity, dyslipidemia, elevated blood pressure and insulin resistance [2]. Recently, MetS has been considered to play an important role in the development and progression of BPH/LUTS [3,4,5]. Although the exact pathophysiological mechanism between MetS and BPH/LUTS remains unclear, emerging evidence has shown that chronic inflammation is a candidate mechanism at the crossroad between MetS and BPH/LUTS [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1. Finally, 16 studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were included in this meta-analysis. Table 1 summarizes the main characteristics of included studies involving 1895 cases of BHP patients with MetS and 2224 cases of BHP patients without MetS.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of BPH has intrigued researchers in various fields of medicine. Some of them suggested that metabolic syndrome is significantly associated with the development of BPH [3,4]. BPE usually involves the hypertrophy of all elements of prostate.…”
Section: Introductionmentioning
confidence: 99%